2018
DOI: 10.1080/2162402x.2017.1415687
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer-associated cancer-testis antigen-derived long peptides encompassing both CTL and promiscuous HLA class II-restricted Th cell epitopes induced CD4+ T cells expressing converged T-cell receptor genes in vitro

Abstract: DEP domain containing 1 (DEPDC1) and M-phase phosphoprotein 1 (MPHOSPH1) are human cancer testis antigens that are frequently overexpressed in urinary bladder cancer. In a phase I/II clinical trial, a DEPDC1- and MPHOSPH1-derived short peptide vaccine demonstrated promising efficacy in preventing bladder cancer recurrence. Here, we aimed to identify long peptides (LPs) derived from DEPDC1 and MPHOSPH1 that induced both T-helper (Th) cells and tumor-reactive cytotoxic T lymphocytes (CTLs). Stimulation of periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…Currently, DEPDC1 promoting cancer development was gradually discovered and had been widely considered as a putative oncogene. The role of DEPDC1 in cancers was mainly found in bladder cancer (8, 10, 24, 29, 30). It was reported that DEPDC1 was significantly increased in bladder carcinoma and necessary for the proliferation of cancer cells (8).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, DEPDC1 promoting cancer development was gradually discovered and had been widely considered as a putative oncogene. The role of DEPDC1 in cancers was mainly found in bladder cancer (8, 10, 24, 29, 30). It was reported that DEPDC1 was significantly increased in bladder carcinoma and necessary for the proliferation of cancer cells (8).…”
Section: Discussionmentioning
confidence: 99%
“…Kanehira et al showed that the MPHOSPH1/PRC1 complex might potentially play a critical role in bladder tumorigenesis and that suppression of MPHOSPH1/PRC1 expression or their interaction might be therapeutic targets for bladder cancer [11]. Also, Tsuruta et al showed that a DEPDC1-derived and MPHOSPH1-derived short peptide vaccine showed promising efficacy in reducing relapse of bladder cancer in a phase I/II clinical trial [12]. These findings indicate the potential role for CTAs as immunotherapeutic targets in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among recent preclinical studies dealing with peptide-based anticancer vaccines, we found of particular interest the works of: (1) Zhu and colleagues (from the National Institutes of Health, Bethesda, MD, USA), who developed self-assembling albumin-vaccine nanocomplexes that reportedly enable superior delivery and mediated robust therapeutic effect against transplantable tumors growing in immunocompetent mice, especially when combined with immune checkpoint blockers and chemotherapy; 94 (2) Gall et al (from the MD Anderson Cancer Center, Houston, TX, USA), who unveiled a Fc receptor-mediated mechanism whereby the FDA-approved HER2-targeting mAB trastuzumab favors the uptake of a HER2-targeting vaccine by DCs, resulting in efficient cross-presentation of its immunodominant epitope in vivo and robust therapeutic effects against breast carcinoma; 171 (3) Tsuruta et al (from Kumamoto University, Kumamoto, Japan), who developed DEP domain containing 1 (DEPDC1)- and M-phase phosphoprotein 1 (MPHOSPH1)-derived synthetic long peptides (SLPs) that efficiently induce both helper T (T H ) cells and CTLs in vitro and in vivo ; 172 (4) Petrizzu and collaborators (from the Istituto Nazionale per lo Studio e la Cura dei Tumori, Naples, Italy), who showed that metronomic chemotherapy plus a PD-1-targeting immune checkpoint blocker are highly efficient in potentiating the antitumor effects of a multi-peptide vaccine in a mouse model of melanoma; 173 and (5) Tanaka and co-workers (from the Yamaguchi University, Ube, Japan), who demonstrated that miR-125b-1 and miR-378a expression levels may be harnessed to predict the efficacy of peptide-based vaccination against colorectal carcinoma. 174 …”
Section: Literature Updatementioning
confidence: 99%
“…A large majority of these studies involve either short TAA-derived peptides that can directly bind to MHC Class I or II molecules expressed by antigen-presenting cells 176 (42 studies), or SLPs that are processed intracellularly and then loaded on MHC Class I or II molecules 172,177,178 (22 studies), most often in combination with immunological adjuvants 179-182 like montanide ISA-51 (water-in-oil emulsion) 181,183 Hiltonol® (poly- L -lysine in carboxymethylcellulose, a TLR3 ligand) 184 and GM-CSF. 183,185-187 In several instances, vaccination is further combined with standard treatment regimens including conventional chemotherapy, 117,188-191 radiation therapy, 52,192-195 and targeted anticancer agents, 196-199 or with various immunotherapeutic interventions.…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%